2018
DOI: 10.1021/acs.est.8b02599
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Centered Metagenomics Analysis Reveals the Symbiotic Organisms Possessing Ability to Cross-Feed with Anammox Bacteria in Anammox Consortia

Abstract: Although using anammox communities for efficient wastewater treatment has attracted much attention, the pure anammox bacteria are difficult to obtain, and the potential roles of symbiotic bacteria in anammox performance are still elusive. Here, we combined long-term reactor operation, genome-centered metagenomics, community functional structure, and metabolic pathway reconstruction to reveal multiple potential cross-feedings during anammox reactor start-up according to the 37 recovered metagenome-assembled gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(93 citation statements)
references
References 56 publications
10
81
2
Order By: Relevance
“…The recovered abundant and/or active heterotrophs in the PNA reactor were denitrifying bacteria and provided extra nitrite/ammonium for anammox bacteria via the nitrite/ammonium loop, which was also identified in previous works [17, 20, 68]. Therefore, the assemblages of bacteria may be selected not only by the operational modes but also by the key metabolism process in the studied system.…”
Section: Resultssupporting
confidence: 63%
“…The recovered abundant and/or active heterotrophs in the PNA reactor were denitrifying bacteria and provided extra nitrite/ammonium for anammox bacteria via the nitrite/ammonium loop, which was also identified in previous works [17, 20, 68]. Therefore, the assemblages of bacteria may be selected not only by the operational modes but also by the key metabolism process in the studied system.…”
Section: Resultssupporting
confidence: 63%
“…Numerous studies of anammox bioreactors revealed complex microbial communities comprising, in addition to dominant anammox planctomyctes, a number of such physiological groups, as fermentative bacteria, nitrifiers, denitrifiers, methanogens, and others (Hu et al, 2012; Gonzalez-Martinez et al, 2015a; Speth et al, 2016; Mardanov et al, 2017; Park et al, 2017; Zhao Y. et al, 2018). In order to get deeper insights into microbial community composition and reveal minor community members for which MAGs were not assembled, we analyzed raw pyrosequencing reads.…”
Section: Resultsmentioning
confidence: 99%
“…Filamentous bacteria of the phylum Chloroflexi usually account for a significant part of the microbial community of anammox-based bioreactors (Kindaichi et al, 2012; Chu et al, 2015; Wang et al, 2017) and were also detected in this study both by metagenomics and FISH analysis (Figures 2A,B). It is hypothesized that in anammox bioreactor communities Chloroflexi are involved in the degradation of organics from dead cells, or they can be involved in the synthesis or degradation of extracellular polymeric matrix (Ni et al, 2012; Speth et al, 2016; Zhao Y. et al, 2018). Due to their filamentous structure, they play an important role in the formation of biofilms (Kindaichi et al, 2012; Zhao Y. et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although the microbial ecology of anammox granules was studied in previous studies [22,23,25,49,50], the size-fractioned anammox granule system proposed here delineates the interactions among granules with different sizes from micro-scale view for the first time. In a recent study, the crossfeeding among microorganisms was investigated based on metagenomics analysis [50]. However, the present study touched another dimension to demonstrate the interactions between granules based on more comprehensive data (metagenomics and metatranscriptomics).…”
Section: Integrating Nitrogen Cycling Microorganism and Activities Inmentioning
confidence: 99%